2007
DOI: 10.1016/j.juro.2007.03.039
|View full text |Cite|
|
Sign up to set email alerts
|

Indwelling Ureteral Stents and Sexual Health: A Prospective, Multivariate Analysis

Abstract: Ureteral stents impaired the quality of sexual life in male and female subjects. In men the most important distress was in regard to erectile function, probably related to lower urinary tract symptoms. Conversely female sexuality appeared to be severely impaired due to stent related psychological concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 19 publications
0
44
1
Order By: Relevance
“…Kogan, Mojsjuk, Shkodkin, Sajdulaev, and Idashkin (2015) observed that bladder irritability was encountered due to the shape of the JJ catheter rather than the presence of urinary infection. Sighinolfi et al (2007) argued that longer catheterisation times significantly affect sexual function compared to short-term catheterisation. Significant emotional and physical morbidity may be seen in patients due to JJ stents (Joshi et al, 2003a,b (Srivastava, Gupta, Kumar, Kapoor, & Mandhani, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kogan, Mojsjuk, Shkodkin, Sajdulaev, and Idashkin (2015) observed that bladder irritability was encountered due to the shape of the JJ catheter rather than the presence of urinary infection. Sighinolfi et al (2007) argued that longer catheterisation times significantly affect sexual function compared to short-term catheterisation. Significant emotional and physical morbidity may be seen in patients due to JJ stents (Joshi et al, 2003a,b (Srivastava, Gupta, Kumar, Kapoor, & Mandhani, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study focused on the relation between stents and sexual dysfunction(Sighinolfi, Micali, De Stefani, Mofferdin, and Grande (2007). Patients may suffer from symptoms related to JJ stents, such as intolerance to the stent, depression, severe stent-related pain, haematuria or urgency.…”
mentioning
confidence: 99%
“…Despite the usefulness of double-J stent, some of the patients might encounter stent-related morbidities such as urinary tract infection (UTI), lower urinary tract symptoms (LUTS), stent-related body pain, and hematuria. These symptoms represent a prevalent problem with considerable effects on the quality of life, substantial general health, work performance, and sexual matters in both genders [35]. The pathophysiology of stent-related symptoms remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The Ureteral Stent Symptom Questionnaire (USSQ) looks at different facets of life including sexual function which has been shown to be negatively affected by the presence of a stent (Sighinolfi, Micali et al 2007). In fact, ureteroscopes, intracorporeal lithotriptors, and ureteroscopic techniques have improved to the point that the major morbidity of ureteroscopy has become the stent left in situ postoperatively.…”
Section: Problems Arising From Stentsmentioning
confidence: 99%